Media Motung (Monster Hitung) untuk Kemampuan Berhitung Siswa Kelas 1 Sekolah Dasar - Listiana, Erma Okta (Caruban: Jurnal Ilmiah Ilmu Pendidikan Dasar, 2024)
Based on the results of PISA (Program for International Student Assessment) released by the OECD, of the 79 countries that joined PISA, Indonesia is at level 74 with a low level of numeracy literacy. In mathematics subjects, the basic ability that students must have is the ability to count. The mathematics subject of addition material for grade 1 students must be explained in concrete stages. Media as a learning aid has a very important role in learning. In a preliminary study at SDN 1 Nawangan, several problems related to the media were found. Where the existing media is not yet in accordance with the characteristics of grade 1 elementary school students who think concretely. Based on this problem, researchers conducted research with the aim of seeing how Motung media was developed to help the learning process in class 1. The method used was Rnd (research and development). The result of this research is a product, namely learning media called Motung or counting monster which is used for learning mathematics, addition material.